Amount of generators of reactive oxygen species as a marker of organism damage on the background of experimental limb ischemia-reperfusion - Volotovska, Nataliya (Journal of Education, Health and Sport, 2021)
Massive blood loss resulting in hemorrhagic shock requires the use of a hemostatic tourniquet. According to the literary sourced using of tourniquet for 2 hours is safe, but the newest investigations have shown ambiguous consequences for the body, coused by both local changes in the tissues under the tourniquet’s pressure, and the outflow of metabolic products into the general bloodstream from primarly ischemic limb. The aim was to identify the interralation between the level of production of reactive oxygen species by neutrophils of peripheral blood due to ischemia-reperfusion of the limb, as well as its combination with volumetric blood loss or mechanictal trauma. Materials and methods. The experiment was perfomed on 260 white male rats (200-250 g), which were divided into 5 groups: control, EG-1 – simulation of isolated limb ischemia-reperfusion (IR), EG-2 – simulation of isolated volumetric blood loss, EG -3 – combination of limb IR with blood loss, EG-4 – modeling of isolated thigh mechanical injury, EG-5 – combination of limb IR and mechanical injury. The percentage of neutrophils-producers of reactive oxygen species (ROS) was determined in the blood by flow cytofluometry. Results. It was found that ischemia-reperfusion of the limb, acute massive blood loss and their combination led to an increase in the number of ROS producers in the peripheral blood in all study periods. In the EG-2 on 1st and 3rd days it was higher than in the KG in 2,41 times and in 2,39 times accordingly, and also on 7th day exceeded level of the KG in 2,39 times and remained raised in 2 times on 14th day . In the EG-3 on the 1st day after injury exceeded the CG data in 2,5 times, then slightly decreased and exceeded the CG level in 2,3 times on the 3rd day. However, on the 7th and 14th day the index exceeded the CG level in 2,6 times and 3,3 times. The peculiarities which indicate the effect of mutual burden was that on the 14th day the level of ROS producers in the EG-3 was statistically significantly higher compared to the EG-1 in 3 times, and compared to the EG-2 – by 63,7%. Also, on the 14th day, the level of ROS in the EG-5 was in 2,4 times higher than the data of the EG-1, and by 58,3% higher than the data of the EG-4. In this case, after modeling only the ischemia-reperfusion of the limb, the figure was increased till the 14th day, on which it beame close to the initial rate.